Factors Affecting Traders' Income in the Beringkit Public Market - Ida Bagus Gede Bayu Anasuyakurunandana Manuaba (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Beringkit Public Market is one of the largest markets in Mengwi sub-district. The location of Beringkit Public Market is very strategic because it is close to several regencies/cities in Bali so that access is easier. This Beringkit Market is located close to Badung Public Health Center and Taman Ayun tourist attraction. It has a large parking area for cars, trucks and motorbikes. The market, which has been operating since 1970, still exists today, we can visit here on Wednesdays and Sundays from 08:00 to 17:00. Not all traders at Beringkit Public Market can earn the same income as the Badung UMR. 121 traders are unable to earn enough income to meet family needs due to limited capital and working hours. This study aims to determine whether working hours can affect the income of traders at Beringkit Public Market. The sample in this study was 121 respondents. Data were collected through questionnaires and in-depth interviews. The collected data were analyzed using classical assumption tests, multiple linear regression analysis, coefficient of determination, simultaneous tests, and partial tests. The results of this study indicate that capital has a positive and significant effect on the income of traders at Beringkit Public Market, working hours have a positive and significant effect on the income of traders at Beringkit Public Market, and education has a positive effect on the income of traders at Beringkit Public Market.